2016
DOI: 10.1519/jsc.0000000000001316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Strength Training on Running Economy in Highly Trained Runners: A Systematic Review With Meta-Analysis of Controlled Trials

Abstract: Balsalobre-Fernández, C, Santos-Concejero, J, and Grivas, GV. Effects of strength training on running economy in highly trained runners: a systematic review with meta-analysis of controlled trials. J Strength Cond Res 30(8): 2361-2368, 2016-The purpose of this study was to perform a systematic review and meta-analysis of controlled trials to determine the effect of strength training programs on the running economy (RE) of high-level middle- and long-distance runners. Four electronic databases were searched in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(100 citation statements)
references
References 50 publications
7
86
0
7
Order By: Relevance
“…This lower relative intensity may not require the need to recruit higher threshold motor units, where the muscle energy cost is higher. This may be one of the explanations by which E run is improved following a period of strength training (Balsalobre-Fernandez et al, 2016; Berryman et al, 2017). However, any additional muscle mass that is not used during running results in essentially wasted energy, since carrying that mass will cost energy.…”
Section: Factors Affecting Erun That Are Altered By Trainingmentioning
confidence: 94%
“…This lower relative intensity may not require the need to recruit higher threshold motor units, where the muscle energy cost is higher. This may be one of the explanations by which E run is improved following a period of strength training (Balsalobre-Fernandez et al, 2016; Berryman et al, 2017). However, any additional muscle mass that is not used during running results in essentially wasted energy, since carrying that mass will cost energy.…”
Section: Factors Affecting Erun That Are Altered By Trainingmentioning
confidence: 94%
“…Similar to previous studies with soccer players (36), time to exhaustion in the 20-m multistage shuttle run test was equally improved in both the PJT-B and PJT-A groups after plyometric training ( Table 3). The observed improvements in endurance due to plyometric training might have occurred due to neuromuscular-mediated changes in athletes' running efficiency (5,45), neuromechanical improvements (21) and increased tendon stiffness. This can allow a faster transfer of force from contracting muscles to moving bones via tendons (18), reducing reaction times (25) and positively affecting athletes' ability to change direction This is the first study to demonstrate that both PJT-B and PJT-A induced a greater (p<0.05) increase in 20-m multistage shuttle run test times compared to a control group (Table 3).…”
Section: ***mentioning
confidence: 99%
“…Numerous studies have explored the influence of chronic (ranging from 4 to 14 weeks) plyometric and/or resistance training interventions on RE and running performance (Spurrs et al, 2003;Guglielmo et al, 2009;Berryman et al, 2010). Balsalobre-Fernández et al (2016) suggested it is optimal and practical for highly trained endurance athletes to perform 8-12 weeks' low to high intensity resistance and plyometric training, with a frequency of 2-3 sessions per week, for the purpose of enhancing RE. In contrast, few studies have explored the acute effects of plyometric and resistance warm-up protocols on RE in healthy adults and endurance athletes.…”
Section: Discussionmentioning
confidence: 99%